Comparison of the 'Seattle' and 'International' criteria electrocardiogram interpretation in Division II female collegiate athletes: a preliminary study - Cosio-Lima, L.; Brooke, N. K.; Adlof, L.; Simpson, J.; Crawley, A.; Lee, Y. (Journal of Science in Sport and Exercise, 2023)
Purpose A 12-lead electrocardiogram (ECG) is a screening tool to detect abnormalities that may predispose athletes to sudden cardiac death. Newer standardized criteria have been introduced to better interpret ECG data, however this research has predominantly focused on male athletes. It is important to include female athletes in research to better define ECG characteristics in this population. The purpose of this study was to compare the Seattle and International Criteria ECG abnormalities in Division II female collegiate athletes of various ethnicities.